Про підвищення екологічної безпеки повернення супутньо-пластових вод нафтогазоконденсатних родовищ - Мельник, Анатолій Павлович; Німець, Наталя Миколаївна; Подустов, Михайло Олексійович (НТУ "ХПІ", 2017)
Досліджено зменшення концентрації іонів заліза (ІІ) при одержанні йоду з супутньо-пластових вод нафтогазоконденсатних родовищ України озонуванням, оцінено ступінь перетворення заліза (ІІ) в залізо (ІІІ), встановлено, що при озонуванні суміші іонів Fe²⁺ з іонами J⁻ на залежності ступеня утворення йоду від співвідношенні Fe²⁺/J⁻ спостерігається максимум, до досягнення якого переважно в реакцію вступають іони йоду, що вказує на можливість вилучення йоду з СПВ, озонування прискорює процес перетворення іонів заліза (ІІ) в іони заліза (ІІІ), які коагулюючи випадають у осад разом з завислими речовинами, що покращує процес підготовки супутньо-пластових вод до повернення та впливає на екологічну безпеку.

The decrease in the concentration of iron ions (II) in the preparation of iodine from the fossil groundwater of oil/gas-condensate fields of Ukraine by ozonation has been studied, the degree of conversion of iron (II) to iron (III) has been estimated and it has been established that at ozonizing a mixture of Fe²⁺ ions with J⁻ ions on the dependence of the degree of Fe²⁺/J⁻ iodine formation the maximum is observed upon reaching of which J⁻ ions mainly enter into a reaction, which indicates the possibility of extraction of iodine from the fossil groundwater, the ozonation accelerates the process of conversion of iron ions (II) into iron ions (III), which after coagulation are precipitating with suspended substances, which improves the process of preparing the associated fossil groundwater before the return and has an impact on the environmental safety.
On improving environmental protection of associated formation water return in the interior of the Earth
Keywords: пласт; вода; йодид-іон; йод; озонування; fossil; water; iodide ion; iodine; ozonation; iron; ratio